Effects of Esmolol Infusion on Cardiovascular Parameters and Quality of General Anaesthesia in Younger and Older Patients - Lončar-Stojiljković, Dragana B. (Scripta Medica, 2021)
Background: Esmolol is a cardioselective β-adrenergic antagonist that is used during general anaesthesia to blunt the sympathetic reflex tachycardia and hypertension. The aim of the study was to investigate whether the potential beneficial and adverse effects of esmolol differ depending on the patient age. Methods: A total of 50 ASA I/II patients scheduled for elective upper abdominal surgery were divided in two groups: younger (patients aged up to 35 years) and older (patients older than 65). After premedication with diazepam, they were infused with esmolol during the first 5 min at a rate of 0.3 mg/kg/min and 0.1 mg/kg/min thereafter. Anaesthesia was induced with thiopental sodium 3-5 mg/kg intravenously (iv) and fentanyl 1.5 µg/kg iv. Tracheal intubation was facilitated with suxamethonium 1-2 mg/kg iv. Long-term neuromuscular blockade was induced with pancuronium bromide 0.07 mg/kg iv bolus and maintained with incremental iv boluses of 0.01 mg/kg. Inhalational anaesthesia was maintained with a mixture of oxygen and nitrous oxide (O2/N2O) 2 : 1. Results: The systolic blood pressure remained constant during the intubation phase in the group of older patients, at the same time being around 89 % of the pre-induction values, while in younger patients it rose up to 100 %. During the same phase of anaesthesia, the diastolic blood pressure in older patients remained at about 91 %, while in younger patients it rose up to 107 % of the pre-induction values. The consumption of drugs and the speed and quality of the recovery from anaesthesia did not differ between the two groups of patients. Conclusion: Infusion of esmolol contributes to the concept of general balanced anaesthesia in elective patients scheduled for upper abdominal surgery equally in younger and older patients.